Factors associated with psychological distress among Myanmar residents during COVID-19 pandemic crises - Roy Rillera Marzo; Soe Soe Aye; Thein Win Naing; Thin Mon Kyaw; Myat Thida Win; Htoo Htoo Kyaw Soe; Minn Soe; Ye Wint Kyaw; Maung Maung Soe; Nay Linn (SAGE Publishing, 2021)
Background: COVID-19 pandemic reached a public health emergency status of international concern. The impacts and events associated with this were associated with adverse psychological impacts among the general public globally. This study aimed to determine the prevalence of psychological distress and to identify predictors associated with psychological distress due to the COVID-19 pandemic among the population in Myanmar. Design and Methods: A cross-sectional survey was conducted from March to April 2020 among adults, 18 years old and above, who reside in Myanmar through a structured questionnaire distributed in social media platforms. Univariate and Bivariate analyses were used to estimate the prevalence of COVID-19 Peritraumatic Distress Index (CPDI) symptoms and to test the associations between CPDI and the exposure variables. Logistic Regression Analysis was done to identify significant predictors of distress. Results: There were 530 participants in this study.37.4% of them did not have psychological distress,55.6% experienced mild to moderate psychological distress, and 7% experienced severe psychological distress due to COVID-19 pandemic. Simple and Multiple Logistic Regression Analyses were performed to determine the factors associated with psychological distress due to COVID-19. Conclusions: It was shown that the self-employed group and age group older than 45 years old had more psychological distress than others. However, Buddhists and people from the capital city had less distress than other religions and districts. This study recommends the government to develop better strategies for self-employed groups, elders, and the poor for a support, relief, and resettlement of their ruined status.